FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN TUBERKULOSIS PARU PADA PENDERITA DIABETES MELITUS DI RSUP PERSAHABATAN JAKARTA TAHUN 2020 - Michel Kezia Yosephine, (2021)
People with diabetes are at higher risk for developing active tuberculosis. The DM epidemic has increased the incidence of tuberculosis. The purpose of this study is to determine factors that affect the incidence of lung tuberculosis in diabetic patients at persahabatan hospital in 2020. The method used analytic with case control research design. The sampling technique is purposive sampling and involved 110 respondents using a sample ratio 1:1 for case and control group. Data source in this study is secondary data from patient's medical record. The analysis used is chi square and logistic regression. The variables studied are age, sex, employment, nutritional status, HbA1C levels, and duration of having DM. The result show factors associated with tuberculosis patients are age (p value=0,038; OR=3,068), sex (p value=0,022; OR=2,625), nutritional status (p value=0,013; OR=0,352), and Hb1c level (p value=0,046; OR= 2,440). Based on with the results of multivariate analize factor that have more effects is HbA1C level (Adjusted OR= 3,141; 95%CI= 1,299-7,594). Reccomended for diabetic patients to do healthy diet, regular exercise, comply with DM treatment, and regularly check blood glucose to maintain normal blood glucose levels and carry out active surveillance to the incidence of pulmonary tuberculosis in diabetes mellitus patients with uncontrolled blood glucose levels for health facilities.